Present status of the experimental aspect of RFe2O4 study. (21st January 2015) - Ikeda, Naoshi; Nagata, Tomoko; Kano, Jun; Mori, Shigeo
Abstract: We give a brief review of the experimental research on a triangular mixed valence iron oxide R Fe2 O4 ( R  = Y, Dy, Ho, Er, Tm, Yb, Lu, Sc or In). Interest in this material has been increasing every year because of the fascinating but complicated interaction between spin, charge and the orbital state of iron ions in frustrated geometry. Reports collected in this review cover experimental research on crystallography, chemical analysis, bulk and thin film preparation, magnetic, dielectric, diffraction with neutrons, x-ray and electron, optical and x-ray absorption, Mössbauer spectroscopy and other methods that incorporate the use of modern scientific technology and knowledge. The report mainly focuses on experimental facts since 1990 on which an early review by Siratori has been published (Kimizuka et al 1990 Handbook on the Physics and Chemistry of Rare Earths vol 13, ed K A Gschneidner Jr and L Eyring (Amsterdam: North-Holland/Elsevier) pp 283–384).